Penegakan Hukum Terhadap Tindak Pidana Impor Pakaian Bekas Dari Malaysia ke Indonesia Berdasarkan Undang-Undang No 7 Tahun 2014 Tentang Perdagangan - Tegar Adit Saputra; Ika Ariani; Susilo Wardani; Marsitiningsih Marsitiningsih (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
The circulation of imported used clothing from Malaysia to Indonesia is still found despite being prohibited by law. This practice has the potential to harm the domestic textile industry, disrupt business competition, and pose a risk to public health. The problem in this study is the suboptimal law enforcement against importers and parties involved in the distribution of imported used clothing and to identify the factors that hinder law enforcement. This study aims to analyze the implementation of law enforcement against the crime of importing used clothing based on Law Number 7 of 2014 concerning Trade and examine the factors that hinder its effectiveness. The research method used is a combined legal research, namely normative and empirical research with a statutory, conceptual, and sociological approach. The results show that law enforcement has been carried out through preventive and repressive efforts by the Directorate General of Customs and Excise together with related agencies, but has not been optimal due to limited supervision, difficulties in proving the origin of goods, and high demand for imported used clothing. Therefore, it is necessary to strengthen inter-agency coordination, increase supervision, and enforce the law more firmly to achieve legal certainty and protection for the domestic industry.